Reliability and maintenance analysis of two-component system subject to zoned shocks and degradation processes - Zhang, Yamei; Zhao, Songzheng; Wu, Bei (Reliability engineering & system safety, 2025)
System failures are frequently attributed to internal degradation or external shocks, however, not all shocks lead to harmful effects on the system. This paper explores a reliability assessment and two different maintenance strategy models for the serial system composed of two distinct components, each subjected to natural degradation and zoned shocks. Specifically, the effect of shocks on the system is categorized into four zones across various magnitudes, with different components eliciting different shock models. Building upon this framework, a reliability model for two-component system is developed and subsequently extended to multi-component configurations. In addition, a system reliability simulation algorithm based on the Monte Carlo method is proposed and further enhanced to accommodate dynamic environments by applying a semi-Markov process. Concurrently, in alignment with the system’s failure model, two different maintenance strategies are proposed to determine optimal preventive and corrective maintenance intervals, namely: reliability-centered and shock-based approaches. Finally, a practical example involving a rotor–stator system is utilized to demonstrate the application of the proposed model and methodologies. •Two-component system subject to competing failure processes is studied and extended.•Explicit formulas and simulation algorithms for reliability indexes are provided.•A reliability-centered and shock-based maintenance optimization models are proposed.•A case study of rotor-stator system to demonstrate models and results is presented.